Embryogenesis and early skeletogenesis in the antarctic bullhead notothen, Notothenia coriiceps. Issue 11 (29th August 2016) - Postlethwait, John H.; Yan, Yi‐lin; Desvignes, Thomas; Allard, Corey; Titus, Tom; Le François, Nathalie R.; Detrich, H. William
Abstract : Background: Environmental temperature influences rates of embryonic development, but a detailed staging series for vertebrate embryos developing in the subzero cold of Antarctic waters is not yet available from fertilization to hatching. Given projected warming of the Southern Ocean, it is imperative to establish a baseline to evaluate potential effects of changing climate on fish developmental dynamics.Results: We studied the Bullhead notothen ( Notothenia coriiceps ), a notothenioid fish inhabiting waters between ‐1.9 and +2 °C. In vitro fertilization produced embryos that progressed through cleavage, epiboly, gastrulation, segmentation, organogenesis, and hatching. We compared morphogenesis spatially and temporally to Zebrafish and medaka. Experimental animals hatched after about 6 months to early larval stages. To help understand skeletogenesis, we analyzed late embryos for expression of sox9 and runx2, which regulate chondrogenesis, osteogenesis, and eye development. Results revealed that, despite their prolonged developmental time course, N. coriiceps embryos developed similarly to those of other teleosts with large yolk cells.Conclusions: Our studies set the stage for future molecular analyses of development in these extremophile fish. Results provide a foundation for understanding the impact of ocean warming on embryonic development and larval recruitment of notothenioid fish, which are key factors in the marine trophic system. Developmental Dynamics 245:1066–1080, 2016 . © 2016 Wiley Periodicals, Inc. Key findings: We followed in detail, from fertilization until hatching, the developmental progression of Bullhead notothen ( Notothenia coriiceps ), a benthic red‐blooded notothenioid fish inhabiting the icy waters of Antarctica, including the Antarctic Peninsula, the most rapidly warming part of the globe. Despite developing below the freezing point of fresh water, notothen embryos progressed with morphologies similar to other well‐studied fish embryos, but at a much slower rate. In situ hybridization experiments on the robustly mineralized skeletons of notothen embryos showed that genes encoding the key skeletogenesis regulatory factors Sox9 and Runx2 were expressed in a fashion similar to orthologs in other well mineralized fish, providing a baseline for investigation of Antarctic icefish with osteopenic skeletons. Results provide a schedule of normal embryonic development essential for evaluating the effects of the warming of the Southern Ocean on long‐term survivability of Antarctic fish.